Categories of incubator success: a case study of three New York incubator programmes. Issue 1 (5th January 2015) - Al-Mubaraki, Hanadi Mubarak; Muhammad, Ali Husain; Busler, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate and identify three categories of incubators in the USA located in New York (NY). The incubator categories are: technology commercialisation; economic development; and entrepreneurship. Design/methodology/approach – The study uses a qualitative approach based on interviews concerning three incubator programmes selected for their successful outcomes. Findings – The research findings suggest four priorities for incubators: to be dynamic models of self-sustainable, efficient business development; to provide helpful tools for generating jobs; to foster and support enterprise and innovation to create the best environment for the start-up and smart growth of businesses; and to support value-added businesses through various means, such as developing the region's science parks and R&D centres, improving collaboration between universities, and supporting business investment and growth. Originality/value – The research adds value to academicians and practitioners such as government, funded organisations, institutions and policy makers.